The Effect of Green Innovation and Eco-Efficiency on Financial Performance with Good Corporate Governance as A Moderating Variable - Komang Cyntia Utami; Ni Putu Budiadnyani (Journal Research of Social Science, Economics, and Management, 2025)
This study examines the influence of green innovation and eco-efficiency on financial performance with good corporate governance (GCG) as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2022-2024. The research employs quantitative methods using Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis with a sample of 180 observations from energy sector companies over three years selected through purposive sampling. The results indicate that green innovation negatively and significantly affects financial performance, while eco-efficiency positively and significantly impacts financial performance. Furthermore, GCG weakens the influence of green innovation on financial performance but strengthens the positive influence of eco-efficiency on financial performance. These findings provide insights for companies in balancing environmental innovation with operational efficiency under effective corporate governance to optimize financial performance in the energy sector.